2011
DOI: 10.2337/dc10-2206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Optimization of Therapeutic Footwear for Neuropathic Diabetic Foot Patients Using In-Shoe Plantar Pressure Analysis

Abstract: OBJECTIVETherapeutic footwear for diabetic foot patients aims to reduce the risk of ulceration by relieving mechanical pressure on the foot. However, footwear efficacy is generally not assessed in clinical practice. The purpose of this study was to assess the value of in-shoe plantar pressure analysis to evaluate and optimize the pressure-reducing effects of diabetic therapeutic footwear.RESEARCH DESIGN AND METHODSDynamic in-shoe plantar pressure distribution was measured in 23 neuropathic diabetic foot patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
180
1
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(202 citation statements)
references
References 16 publications
(23 reference statements)
5
180
1
16
Order By: Relevance
“…In terms of pressure distribution, Bus et al [17] demonstrated that peak pressure of diabetic feet was more than 600kPa in a specific MTH area; meanwhile Bus et al [18] also recommended that mean pressure 100kPa or peak pressure 200kPa shall be selected as target for pressure relieving. So in our study, we set two numbers as criterion: one is the 100% of healthy counterpart; another is the 120% of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of pressure distribution, Bus et al [17] demonstrated that peak pressure of diabetic feet was more than 600kPa in a specific MTH area; meanwhile Bus et al [18] also recommended that mean pressure 100kPa or peak pressure 200kPa shall be selected as target for pressure relieving. So in our study, we set two numbers as criterion: one is the 100% of healthy counterpart; another is the 120% of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of the studied articles, 7 studies investigated the effect of footwear on plantar pressure in diabetes patients that one article was systematic review [16], 2 case control [17,18], 2 RCT [19,20] and 1 article review [7]. In one cohort study [21], the impact of sandals in reducing plantar pressure in most areas of foot was higher in comparison to shoes.…”
Section: Plantar Pressurementioning
confidence: 99%
“…A good example of this can be considered the transposition in terms of the prescribing procedure described by Henderson and Lamoreux of the therapeutic footwear optimizing process for patients with diabetic neuropathy described by Sicco A. Bus and others [37]. Thus for therapeutic footwear prescribed by a specialist in physical and rehabilitation medicine the following elements can be formulated: -"medical objective": reducing the risk of ulceration,…”
Section: Practice Of Medical Devices Prescriptionmentioning
confidence: 99%